Clinical Indicators of Robotic Assisted versus Conventional Spine Surgery: A Systematic Review - Hanny Ayu Soegihwangi; Masyitoh Basabih; I Made Esa Sadana Yoga (Masters Program in Public Health, 2026)
Background: Spine surgery has technological breakthrough of robotic assistance systems. The objective of this review is to explore clinical outcome indicators employed for comparison of out-comes of robotic assisted surgery to conventional spine surgery under the framework of evidence-based practice. Subjects and Method: Based on guidelines issued by PRISMA, we systematically searched multi-ple sources, including PubMed, Scopus, and Science Direct databases. Studies comparing robotic assisted and conventional spine surgery were screened and analysed. Clinical indicators were collected and categorized according to surgical, functional, and safety concerns. Results: The 24 review papers reviewed were all published during 2017 – 2025. The study design studies included three RCTs, nineteen RC studies, one prospective controlled study and one PSMC study pointing to the recent incorporation of robotic technologies in spinal surgery. This has revealed five categories of clinical indicators: accuracy benchmarks, operative parameters, safety and complications, functional outcomes, recovery and hospitalization. The most often reported indicator was the precision of the placement of the pedicle screw, followed by time of operation and intraoperative blood loss. Radiation exposure is a very important measure of occupational health and safety. The goal of this comprehensive clinical framework is to identify a method whereby an evidence-based clinical practice framework for efficient application of technological adoption becomes possible which is in favour of sustainable use can help to guide fiscally responsible adoption. Conclusion: The current review establishes a composite framework of clinical indicators of clinical considerations towards robotic versus conventional spine surgery across robotic versus conventional spine surgery, a comprehensive evaluation paradigm. This framework provides a foundation upon which future studies can proceed.